KARAKTERISTIK PENDERITA KANKER SERVIKS - Simangunsong, Anry F. P.; Simangunsong, Batara; Silitonga, Hendrika (Jurnal Kedokteran Methodist, 2019)
Background : Cervical cancer is a cancer that occurs in the cervix and one of them is cervical cancer which causes many deaths in women. Patients have different characteristics with different age, education, occupation, and smoking. This study aims to determine the characteristics of cervical cancer sufferers. The results of this study are that the patient’s age is more at the age of 26-30 years, the level of education is more with high school education. It is recommended that health workers provide counseling or counseling to cervical cancer sufferers and cervical cancer sufferers themselves are expected to immediately re-control the disease if there are complaints related to the disease so that it does not continue to get worse. Method: This study is a study using the literature study method or literature review. This data is obtained from secondary data using documentation techniques. Data documentation is carried out based on journals related to research variables.